Demonstration of Interposed Modular Hydrogel Sheet for Multicellular Analysis in a Microfluidic Assembly Platform - Chae Yun Bae (Nature Portfolio, 2017)
Abstract Hydrogel sheets have emerged as a promising biomaterial scaffold for the encapsulation and transfer of multicellular structures. Although the improvement of the chemical interactions and the design of micro-scaled geometry have contributed to the development of multipurpose hydrogel scaffolds, the application of hydrogel sheets to assess multicellular structures is still challenging. To expand the technical applicability of hydrogel sheets, we here demonstrate that a single layer of the hydrogel sheet can be integrated as an interposed module in a microfluidic device for multicellular analysis. As a cell culture unit, encapsulated pancreatic insulinoma (MIN6) cells in the hydrogel sheet were labeled and examined via multiple microchannels. After obtaining simultaneously multi-labeled cells in the hydrogel sheet that had been incorporated into the microfluidic device, each modular hydrogel sheet was also recoverable and re-cultured without any distortion. The modular hydrogel sheet can be simply manipulated and conserved as a multicellular module in a three-dimensional (3D) in vitro culture platform. Using the modular concept of hydrogel sheets capable of cell culture and/or assay, an integrated multicellular analysis in the microfluidic device is expected to improve accessibility, scalability, and practicality for end users.